A composite electrolyte for regulating the local microenvironment of a water-based battery, a preparation method and applications thereof

CN123018170APending Publication Date: 2026-10-30SOUTH CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511405895.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,锌负极在液态电解质中面临枝晶生长(>1μm/cycle)、析氢腐蚀(HER起始电位<-0.6V)及界面副反应(库伦效率<95%)等问题,导致循环寿命较短

Benefits of technology

[0028]本发明相比于利用分子设计和创新的合成技术让单一添加剂实现功能组合势必会提高成本和技术难度,使用双添加剂既能降低成本,又能简化操作。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005620081430000011
    Figure HDA0005620081430000011
  • Figure HDA0005620081430000012
    Figure HDA0005620081430000012
  • Figure HDA0005620081430000013
    Figure HDA0005620081430000013
Patent Text Reader

Abstract

This invention discloses a composite electrolyte for regulating the local microenvironment of aqueous batteries, its preparation method, and its application. By adding two additives to the electrolyte to synergistically form a solid electrolyte membrane at the negative electrode, multiple protections for zinc batteries can be achieved. The additives contain sucrose, phosphate, and other particles, which disrupt and alter the original hydrogen bond structure, reducing the number of strong hydrogen bonds and increasing the number of non-hydrogen-bonded and weak hydrogen bonds. Simultaneously, an organic-inorganic hybrid Zn3(PO4)2-ZnCO3-ZnO electrolyte membrane is formed to reduce SO42- in the double layer. 2‑ The presence of H2O inhibited water decomposition and the formation of basic zinc sulfate, reducing the formation of dendrites and byproducts. The assembled Zn-I2 battery operated at 0.2 A·g ‑1 The battery achieved a capacity retention rate of 94.1% during cycling, effectively improving its reversibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aqueous zinc-ion batteries, and particularly to the field of electrolyte technology, specifically to a composite electrolyte for regulating the local microenvironment of aqueous batteries, its preparation method, and its application. Background Technology

[0002] Due to their economic viability, environmental friendliness, and high safety, rechargeable aqueous zinc-based energy storage devices are considered one of the most promising energy storage systems for large-scale application in clean energy. Aqueous zinc-ion batteries boast a high theoretical capacity (5855 mAh / cm³). - 3) Intrinsic safety (non-flammable electrolyte) and low cost make zinc a promising candidate technology for large-scale energy storage. However, zinc anodes face challenges in liquid electrolytes, including dendrite growth (>1μm / cycle), hydrogen evolution corrosion (HER onset potential <-0.6V), and interfacial side reactions (coulombic efficiency <95%), resulting in short cycle life. Compared to other complex material preparation processes, finding a modified electrolyte that can positively influence the cathode, anode, and electrolyte itself is currently the most convenient and effective way to address these issues.

[0003] Therefore, to obtain long-life and highly stable aqueous zinc-ion batteries, it is essential to focus on electrolyte improvement strategies. Current research on electrolyte modification methods includes using high-concentration salts, electrolyte additives, gel electrolytes, solid electrolytes, and ionic liquids. These methods improve the overall electrochemical performance of the battery by influencing the three factors mentioned above. Among these, electrolyte additive engineering is a novel, effective, and extremely simple method to operate. Summary of the Invention

[0004] To address the aforementioned problems, this invention aims to develop safe, economical, and stable high-performance aqueous zinc-based energy storage devices by screening suitable dual electrolyte additives. To resolve issues such as zinc dendrite formation, corrosion, and cathode dissolution in zinc-based energy storage devices, composite electrolyte modifiers are introduced into the aqueous electrolyte to improve the cycle life and stability of the zinc anode and the electrochemical performance of the cathode. Furthermore, the electrochemical performance of related zinc-based energy storage devices is explored and studied in depth.

[0005] The primary objective of this invention is to provide a method for preparing a composite electrolyte for regulating the local microenvironment of an aqueous battery.

[0006] Another object of the present invention is to provide a composite electrolyte prepared by the above method.

[0007] Another object of the present invention is to provide the application of the above-mentioned composite electrolyte in aqueous zinc-ion batteries.

[0008] Specifically, this invention introduces the organic solute sucrose and the inorganic acid phosphoric acid. Utilizing the steric hindrance effect of sugar molecules, these substances preferentially and uniformly cover and form sites on the zinc anode, allowing for the binding of more phosphoric acid to generate zinc phosphate on the zinc anode surface. This results in an in-situ SEI film of Zn3(PO4)2-ZnCO3-ZnO inorganic components and some soft, amorphous organic components, thereby inducing a flat and dense deposition layer for zinc ions. Simultaneously, zinc phosphate acts as a fast ion channel, accelerating zinc ion migration. The preferential adsorption of sucrose and zinc phosphate reduces SO42- in the electrical double layer. 2- The presence of H2O inhibits the decomposition of water and the formation of basic zinc sulfate, reducing the formation of dendrites and byproducts.

[0009] The objective of this invention is achieved through the following technical solution:

[0010] A method for preparing a composite electrolyte for regulating the local microenvironment of an aqueous battery, characterized in that phosphoric acid and sucrose are added to a ZnSO4 electrolyte and stirred until homogeneous to obtain the composite electrolyte;

[0011] The concentration of the ZnSO4 electrolyte is 1–3 M;

[0012] The amount of phosphoric acid added is such that the concentration of phosphoric acid in the system is 0.02-0.05M;

[0013] The amount of sucrose added is such that the concentration of sucrose in the system is 0.006 to 0.012 M.

[0014] Preferably, the concentration of the ZnSO4 electrolyte is 2M;

[0015] The amount of phosphoric acid added is such that the concentration of phosphoric acid in the system is 0.036M;

[0016] The amount of sucrose added is such that the concentration of sucrose in the system is 0.01M.

[0017] Preferably, the ZnSO4 electrolyte is prepared by adding deionized water to ZnSO4·7H2O and stirring at room temperature to prepare the ZnSO4 electrolyte.

[0018] The method described in this invention produces a composite electrolyte for regulating the local microenvironment of aqueous batteries.

[0019] The application of the composite electrolyte of the present invention is characterized in that it is used in aqueous zinc-ion batteries; the composite electrolyte generates in-situ Zn3(PO4)2-ZnCO3-ZnO inorganic components and an amorphous organic component SEI film at the zinc anode.

[0020] Preferably, the aqueous zinc-ion battery is composed of a positive electrode, a negative electrode, a separator, and the composite electrolyte as described in claim 4.

[0021] Preferably, the positive electrode is made of iodine, the negative electrode is made of zinc, and the separator is a glass fiber membrane.

[0022] Preferably, the positive electrode material is prepared as follows:

[0023] (1) After mixing activated carbon, conductive carbon black and PVDF binder in proportion, grind and stir evenly, add NMP, coat it onto carbon cloth with a scraper, and dry to obtain positive electrode sheet;

[0024] (2) Soak the positive electrode in ZnI2 solution and dry it to obtain iodine positive electrode.

[0025] Preferably, in step (1), the mass ratio of activated carbon, conductive carbon black and PVDF binder is 7:2:1; the thickness of the slurry coated by the scraper is 200μm; the drying temperature is 50~70℃ and the time is 5~10h;

[0026] In step (2), the concentration of the ZnI2 solution is 0.5M, the soaking time is 30-60 min, the drying temperature is 20-50℃, and the drying time is 6-10 h.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects:

[0028] Compared to using molecular design and innovative synthesis techniques to achieve functional combinations with a single additive, which inevitably increases costs and technical difficulty, this invention uses two additives to reduce costs and simplify operations.

[0029] The composite additives added in this invention provide multiple protections for the zinc anode in multiple directions, including reconstructing the hydrogen bonding environment of the electrolyte, generating an interfacial adsorption layer, and generating an in-situ solid electrolyte protective layer. This effectively guides the uniform nucleation of zinc ions and subsequent uniform zinc deposition, effectively inhibits the growth of zinc dendrites, and improves the cycle stability of the zinc anode.

[0030] Compared to electrolytes with single additives or no additives, batteries assembled using this aqueous zinc-ion battery electrolyte exhibit significantly enhanced long-cycle performance and excellent coulombic efficiency and electrochemical performance.

[0031] On the other hand, this composite modified electrolyte exhibits excellent specific capacity when applied to zinc-iodine batteries.

[0032] This invention, by matching the electrolyte with an iodine cathode, can promote the cycle stability of aqueous zinc-halogen batteries and significantly improve their capacity, laying a solid foundation for the development of aqueous zinc-iodine batteries.

[0033] In a practical application of this invention, a zinc-iodine battery assembled with the modified electrolyte can stably power a small fan. Simultaneously, the assembled zinc-iodine pouch battery can achieve a power output of 0.2 A·g. -1 At a current density of 780 cycles, compared to zinc sulfate electrolyte which short-circuits after 280 cycles, the composite electrolyte significantly improves the cycle stability of the zinc-iodine battery. Attached Figure Description

[0034] Figure 1 Symmetric Zn||Zn symmetric cells with different sucrose concentrations prepared in Example 1 of this invention were tested at 10 mA / cm². -2 5mAh cm -2 Voltage-time curves under test conditions.

[0035] Figure 2 The symmetrical Zn||Zn battery with different additive electrolytes prepared in Example 2 of this invention was tested at 5 mA / cm². -2 1mAh cm -2 Voltage-time curves under test conditions.

[0036] Figure 3 The asymmetric Zn||Cu battery with different additive electrolytes prepared in Example 3 was tested at 2 mA cm⁻¹. -2 0.5mAh cm -2 Cyclic performance test graph under test conditions.

[0037] Figures 4(a) and (b) show the impedance of the symmetrical battery with four electrolytes assembled in Example 4, tested at four temperatures of 40-50-60-70℃, and the calculated activation energy comparison.

[0038] Figure 5 In Example 5, zinc-iodine batteries with different electrolytes were used at a current density of 0.2 A g. -1 A comparison chart of cyclic performance under the test conditions.

[0039] Figure 6 For the symmetrical battery assembled using PA+Suc in Example 6, at 0.5 mA cm -2 0.5mAh cm -2 The Tem plot after 30 hours of cycling under certain conditions.

[0040] Figure 7 This is a comparison chart of the cycle performance of zinc-iodine soft-pack batteries with added sucrose phosphate composite electrolyte and added ZS electrolyte in Example 7.

[0041] Figure 8Zn||Zn symmetric cells prepared with glucose phosphate electrolyte and sucrose phosphate electrolyte of the same concentration as those in Comparative Example 1 were tested at 20 mA cm⁻¹. -2 10mAh cm -2 Voltage-time curves under test conditions. Detailed Implementation

[0042] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.

[0043] Example 1

[0044] An exploration of the concentration of a composite electrolyte for regulating the local microenvironment of an aqueous battery: 2.875 g of ZnSO4·7H2O was weighed and placed in a beaker, and 3740 μL of deionized water was added. The mixture was stirred at room temperature for 10 min to prepare a 2 M ZnSO4 electrolyte (ZS). 11 μL of phosphoric acid was added using a pipette and dissolved in the prepared 2 M ZnSO4 electrolyte to obtain a phosphoric acid electrolyte (PA). 0.0102 g, 0.0137 g, 0.0171 g, and 0.0205 g of sucrose were weighed and dissolved in the prepared PA electrolyte to obtain sucrose phosphate electrolytes of different concentrations (denoted as 0.036 M PA + 0.006 M Suc, 0.036 MPa + 0.008 M Suc, 0.036 MPa + 0.01 M Suc, and 0.036 M PA + 0.012 M Suc, respectively). The electrolyte was magnetically stirred for 30 minutes at room temperature. Four different concentrations of electrolyte were used as controls. Zn||Zn symmetric cells were assembled using 100-micron thick, 14-mm diameter commercial zinc foil as electrodes and a 16-mm diameter glass fiber membrane as a separator. Testing was performed using the Xinwei testing system. Figure 1 As shown, at 10mA cm -2 5mAh cm -2 Under the specified conditions, the cycling times in 0.036M PA+0.006M Suc, 0.036M PA+0.008M Suc, and 0.036MPA+0.012M Suc were 290h, 285h, and 160h, respectively. 0.036MPA+0.01M Suc exhibited a stable cycling time of 640h at high current density and showed the lowest polarization voltage, thus it was chosen as the optimal concentration for the composite additive.

[0045] Example 2

[0046] A composite electrolyte for regulating the local microenvironment of aqueous batteries: 2.875 g of ZnSO4·7H2O was weighed and placed in a beaker, and 3740 μL of deionized water was added. The mixture was stirred at room temperature for 10 min to prepare a 2M ZnSO4 electrolyte (ZS). 11 μL of phosphoric acid was added using a pipette and dissolved in the prepared 2M ZnSO4 electrolyte to obtain a phosphoric acid electrolyte (PA). 0.0171 g of sucrose was weighed and dissolved in the prepared 2M ZnSO4 electrolyte to obtain a sucrose electrolyte (Suc). 11 μL of phosphoric acid was added using a pipette, and 0.0171 g of sucrose was dissolved in the ZS electrolyte to obtain a phosphate-sucrose composite modified electrolyte (PA+Suc). The electrolyte was magnetically stirred at room temperature for 30 min. The four electrolytes described above were used as electrolytes in aqueous zinc-ion batteries. Commercial zinc foil with a thickness of 100 micrometers and a diameter of 14 mm was used as the electrode, and a glass fiber membrane with a diameter of 16 mm was used as the separator to assemble a Zn||Zn symmetric cell. Testing was conducted using the Xinwei testing system. Figure 2 As shown, at 5mA cm -2 Current density and 1mAh cm -2 Under the specified capacity conditions, symmetrical battery constant current charge-discharge tests were conducted. In this embodiment, the modified composite electrolyte (PA+Suc) exhibited a cycle time of 5400 h superior to that of single additives and ZS under these test conditions, and its polarization voltage was as low as 48 mV, demonstrating good cycle performance. This indicates that the composite electrolyte can achieve highly reversible zinc deposition / stripping.

[0047] Example 3

[0048] The four electrolytes prepared in Example 2 were used as electrolytes in aqueous zinc-ion batteries. Commercial zinc foil with a thickness of 100 micrometers and a diameter of 14 mm was used as the electrode, and a glass fiber membrane with a diameter of 16 mm was used as the separator to assemble a Zn||Cu asymmetric battery. Testing was performed using the Xinwei testing system. Figure 3 As shown, at 2mA cm -2 The current density and 0.5 mAh cm⁻¹ -2 Under the specified capacity conditions, constant current charge-discharge tests were conducted on zinc-copper batteries. The composite electrolyte maintained an average coulombic efficiency of up to 99.35% after 4420 cycles, while the battery with the single additive and ZS electrolyte exhibited poor cycle stability and a relatively fast failure rate, with a rapid drop in coulombic efficiency after only 475, 442, and 525 cycles.

[0049] Example 4

[0050] Figures 4(a) and (b) show a comparison of the activation energies of zinc-ion batteries with the four electrolytes prepared in Example 2, obtained by electrochemical impedance spectroscopy (EIS) tests conducted at 40-70°C. Compared to ZS (41.15 kJ mol), the activation energies are significantly higher. -1 ), Suc (36.82 kJmol) -1 PA (36.67kJ mol) -1 The activation energy exhibited by the Zn electrode in the composite electrolyte is lower than that of the Zn electrode in the Zn electrode (29.12 kJ / mol). -1 This indicates that the PA+Suc additive significantly improved the desolventizing ability and accelerated the desolventizing of Zn. 2+ The transfer process.

[0051] Example 5

[0052] Activated carbon, conductive carbon black, and PVDF binder were weighed, mixed, ground, and stirred evenly in a weight ratio of 7:2:1. NMP (N-methylpyrrolidone) was added, and the mixture was coated onto carbon cloth with a scraper to a thickness of 200 μm. The slurry was dried in a vacuum oven at 60°C for 8 hours. After drying, an electrode sheet with a radius of 1.4 cm was cut to serve as the iodine-loaded positive electrode sheet. This positive electrode sheet was immersed in a 0.5 M ZnI₂ solution for 40 min, then removed and dried in a vacuum oven at 40°C for 8 hours to obtain the iodine positive electrode. The modified composite electrolyte (PA+Suc) and single-additive electrolyte (ZS, PA, Suc) prepared in Example 2 were used. A glass fiber diaphragm with a radius of 1.6 cm was cut, and the negative electrode was high-purity zinc with a polished surface. Figure 5 As shown, at 0.2A g -1 The full cell was charged and discharged at a current density of 223.7 mAh g⁻¹. The zinc-iodine full cell with modified composite electrolyte (PA+Suc) exhibited a current density of 223.7 mAh g⁻¹. -1 The specific capacity was high, and a capacity retention of 94.1% was achieved during long-term cycling. This good reversibility stems from the dual function of the organic-inorganic hybrid SEI—both suppressing side reactions and dynamically homogenizing Zn. 2+ Flux is used to mitigate capacity decay caused by polarization. In contrast, the significant capacity decay and retention rate of full cells using PA and Suc directly reflect the instability of the zinc anode.

[0053] Example 6

[0054] Figure 6 The diagram shows the SEI composition investigated using transmission electron microscopy (TEM). A Zn||Zn symmetric cell was assembled, with a copper mesh added to the negative electrode side. The results were obtained using a Newway testing system at 0.5 mA cm⁻¹. -2 The current density and 0.5 mAh cm⁻¹ -2Under the specified capacity conditions, a constant current charge-discharge test was performed for 30 cycles. The copper mesh was then removed to observe the SEI composition and morphology. High-resolution transmission electron microscopy images are shown below. Figure 6 In (a) and (b), analysis of the crystal structure from the 5nm image revealed an SEI containing abundant Zn3(PO4)2-ZnCO3-ZnO inorganic components and some amorphous organic components, further confirming the formation of the in-situ SEI. The introduction of sucrose facilitates adsorption with Zn at the anode, forming a soft organic protective layer that can bind more phosphate to form zinc phosphate on the zinc anode surface. The preferential adsorption of sucrose and zinc phosphate reduces SO4 in the electric double layer. 2- The presence of H2O inhibits the decomposition of water and the formation of basic zinc sulfate, reducing the formation of dendrites and byproducts.

[0055] Example 7

[0056] To further verify the commercial value of the composite electrolyte, it was assembled into a pouch cell with a load of 200-300 mg, such as... Figure 7 As shown, the pouch cell containing the composite electrolyte maintained approximately 760 cycles, with its capacity decreasing only from 142 mAh g. -1 Reduced to 131mAh g -1 The ZS battery exhibited a capacity retention rate as high as 89%, and its failure after 280 cycles was mainly due to short circuits caused by zinc electrode corrosion pits and zinc dendrites piercing the separator. This demonstrates that the composite electrolyte can exhibit excellent cycle performance and capacity advantages in full cells, and it also has certain practical application value.

[0057] Comparative Example 1

[0058] The performance of sucrose phosphate was compared using phosphoric acid and glucose as a control. 2.875 g of ZnSO4·7H2O was weighed and placed in a beaker, and 3740 μL of deionized water was added. The mixture was stirred at room temperature for 10 min to prepare a 2M ZnSO4 electrolyte (ZS). 11 μL of phosphoric acid was added using a pipette and dissolved in the prepared 2M ZnSO4 electrolyte. Then, 0.009 g (0.01 M) of glucose was weighed and dissolved in the prepared 2M ZnSO4 electrolyte to obtain a glucose phosphate electrolyte (PA+Glu). The electrolyte was magnetically stirred at room temperature for 30 min. The prepared electrolyte and the sucrose phosphate electrolyte (PA+Suc) obtained in Example 2 were used as electrolytes for an aqueous zinc-ion battery. A Zn||Zn symmetric cell was assembled using commercial zinc foil with a thickness of 100 μm and a diameter of 14 mm as electrodes and a glass fiber membrane with a diameter of 16 mm as a separator. Testing was performed using a Newway testing system. Figure 8 As shown, at 20mA cm -2 Current density and 10mAh cm -2Under the specified capacity conditions, symmetrical constant current charge-discharge tests were conducted. In this comparative example, under the same test conditions, the PA+Suc electrolyte exhibited a better cycle time of 195h than the PA+Glu electrolyte, and its polarization voltage was also as low as 60mV, demonstrating better cycle performance. This indicates that the sucrose phosphate electrolyte can achieve better reversible zinc deposition / stripping at high current densities.

[0059] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a composite electrolyte for regulating the local microenvironment of an aqueous battery, characterized in that, Phosphoric acid and sucrose were added to the ZnSO4 electrolyte and stirred until homogeneous to obtain the composite electrolyte. The concentration of the ZnSO4 electrolyte is 1–3 M; The amount of phosphoric acid added is such that the concentration of phosphoric acid in the system is 0.02-0.05M; The amount of sucrose added is such that the concentration of sucrose in the system is 0.006 to 0.012 M.

2. The method for preparing a composite electrolyte for regulating the local microenvironment of an aqueous battery according to claim 1, characterized in that, The concentration of the ZnSO4 electrolyte is 2M; The amount of phosphoric acid added is such that the concentration of phosphoric acid in the system is 0.036M; The amount of sucrose added is such that the concentration of sucrose in the system is 0.01M.

3. The method for preparing a composite electrolyte for regulating the local microenvironment of an aqueous battery according to claim 2, characterized in that, The ZnSO4 electrolyte is prepared by adding deionized water to ZnSO4·7H2O and stirring at room temperature to prepare the ZnSO4 electrolyte.

4. The composite electrolyte for regulating the local microenvironment of an aqueous battery prepared by the method according to any one of claims 1 to 3.

5. The application of the composite electrolyte according to claim 4, characterized in that, Used in aqueous zinc-ion batteries; the composite electrolyte generates in-situ Zn3(PO4)2-ZnCO3-ZnO inorganic components and an amorphous organic component SEI film at the zinc anode.

6. The application according to claim 5, characterized in that, The aqueous zinc-ion battery is composed of a positive electrode, a negative electrode, a separator, and the composite electrolyte as described in claim 4.

7. The application according to claim 6, characterized in that, The positive electrode is made of iodine, the negative electrode is made of zinc, and the separator is a glass fiber membrane.

8. The application according to claim 7, characterized in that, The positive electrode material is prepared as follows: (1) After mixing activated carbon, conductive carbon black and PVDF binder in proportion, grind and stir evenly, add NMP, coat it onto carbon cloth with a scraper, and dry to obtain positive electrode sheet; (2) Soak the positive electrode in ZnI2 solution and dry it to obtain iodine positive electrode.

9. The application according to claim 8, characterized in that, In step (1), the mass ratio of activated carbon, conductive carbon black and PVDF binder is 7:2:1; the thickness of the slurry coated by the doctor blade is 200μm; the drying temperature is 50~70℃ and the time is 5~10h; In step (2), the concentration of the ZnI2 solution is 0.5M, the soaking time is 30-60 min, the drying temperature is 20-50℃, and the drying time is 6-10 h.